1965
DOI: 10.1152/jappl.1965.20.5.938
|View full text |Cite
|
Sign up to set email alerts
|

Influence of age and sex on exercise cardiac output

Abstract: Exercise cardiac output has been measured by an indirect Fick technique in 94 normal subjects (48 men and 46 women) whose ages ranged from 20 to 85 years. With increasing age, exercise cardiac output was found to be greater despite no such trend in oxygen uptake; in consequence, exercise arteriovenous oxygen difference decreased with age. These trends were seen in both sexes, though the age effects were apparent a decade earlier in men. In addition, in men the heart rate was lower and stroke volume higher with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
1

Year Published

1976
1976
2012
2012

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(29 citation statements)
references
References 0 publications
3
25
1
Order By: Relevance
“…How can the higher aortic flow and hemodynamic parameters in early postmenopausal women as compared with age-matched men be explained? Women have been reported to have proportionally higher cardiac outputs than men because of the lower oxygen-carrying capacity of their blood (lower haemoglobin levels, smaller heart, smaller blood volume), as well as lower peripheral oxygen extraction [16,17,24,25]. Both the above physiologic differences and a higher percentage of body fat and smaller muscle fiber area in women [25], may account for the higher relative work load that 50 Watts was for women as compared to men.…”
Section: Doppler Flow Parametersmentioning
confidence: 99%
“…How can the higher aortic flow and hemodynamic parameters in early postmenopausal women as compared with age-matched men be explained? Women have been reported to have proportionally higher cardiac outputs than men because of the lower oxygen-carrying capacity of their blood (lower haemoglobin levels, smaller heart, smaller blood volume), as well as lower peripheral oxygen extraction [16,17,24,25]. Both the above physiologic differences and a higher percentage of body fat and smaller muscle fiber area in women [25], may account for the higher relative work load that 50 Watts was for women as compared to men.…”
Section: Doppler Flow Parametersmentioning
confidence: 99%
“…1,4 However, peak VO 2 itself is also dependent on factors other than CO, such as muscle deconditioning, motivation, obesity, the age, and gender. 5,6 These confounding factors may explain why some patients with CHF may have a favorable prognosis despite a low peak VO 2 . 7,8 Several previous studies have shown that invasive determination of the CO response to exercise via the thermodilution method in addition to the measurement of peak VO 2 enhances its discriminatory power.…”
mentioning
confidence: 99%
“…Zwiren et al (321) postuiated that aithough the pattern of gen&r differences in the responses to exercise are simdar to the earlier investigations (7,8), the magnitude of the gender differences are smaller, which may indicate a gender difference…”
Section: Mechanisms Responsible For the Age-related Decline In V0maxmentioning
confidence: 78%
“…Haemoglobin concentration is lower in females compared to males irrespective of age or training status (7,8 In an attempt to determine the proportion of the gender-related ciifference in V02max amibutable to difkmnoes in ml, Cureton et ai. (48) withdrew blood frorn healthy males to redua k i r mean [Hb) 14% ( h m 153 g r 1 to 134 g-il), to the same level of heaithy females, matched for physral activity leveL Before [Hb j was reduced, V02max was 47% (1-min-' ) and 1 1.5% (ml-kg1-min1) krger in the maies.…”
Section: ü) -Hwmentioning
confidence: 99%
See 1 more Smart Citation